Cytological and Wet Mount Microscopic Observations Made in Urine of Schistosoma haematobium-Infected Children: Hint of the Implication in Bladder Cancer. (2nd September 2019) - Tetteh-Quarcoo, Patience B.; Akuetteh, Benjamin K.; Owusu, Irene A.; Quayson, Solomon E.; Attah, Simon K.; Armah, Robert; Afutu, Emmanuel; Afrah, Ama; Addo-Osafo, Kantanka; Smith, Cecilia; Gyasi, Richard K.; Ayeh-Kumi, Patrick F.
Abstract : Background . Schistosomiasis is the second major human parasitic disease next to malaria, in terms of socioeconomic and public health consequences, especially in sub-Saharan Africa. Schistosoma haematobium ( S. haematobium ) is a trematode and one of the species of Schistosoma that cause urogenital schistosomiasis (urinary schistosomiasis). Although the knowledge of this disease has improved over the years, there are still endemic areas, with most of the reported cases in Africa, including Ghana. Not much has been done in Ghana to investigate cytological abnormalities in individuals within endemic communities, although there are epidemiologic evidences linking S. haematobium infection with carcinoma of the bladder. Aim . The aim of this study was to identify microscopic and cytological abnormalities in the urine deposits of S. haematobium -infected children. Methodology . Three hundred and sixty-seven (367) urine samples were collected from school children in Zenu and Weija communities. All the samples were examined microscopically for the presence of S. haematobium eggs, after which the infected samples and controls were processed for cytological investigation. Results . S. haematobium ova were present in 66 (18.0%) out of the 367 urine samples. Inflammatory cells (82%, 54/66), hyperkeratosis (47%, 31/66), and squamous cell metaplasia (24%, 16/66) were the main observations made during the cytological examination of the S. haematobium -infected urine samples. Conclusion . Cytological abnormalities in S. haematobium -infected children may play an important role in the severity of the disease, leading to the possible development of bladder cancer in later years, if early attention is not given. Therefore, routine cytological screening for urogenital schistosomiasis patients (especially children) at hospitals in S. haematobium -endemic locations is recommended.